Jatrorrhizine from Rhizoma Coptidis exerts an anti-obesity effect in db/db mice. (15th November 2022) - He, Huan; Deng, Jianling; Yang, Maochun; An, Linjing; Ye, Xiaoli; Li, Xuegang
Abstract: Ethnopharmacological relevance: Obesity is closely related to diabetes. Jatrorrhizine (JAT) from Rhizoma Coptidis (RC) can reduce blood glucose and lipid levels. However, the molecular mechanisms for JAT's anti-obesity effect are still not clear. Aim of the study : To explore the effect of JAT in the treatment of obesity and the underlying molecular mechanisms. Materials and methods: db/db mice were used as a typical obese animal model in current study. The anti-obesity effects of five alkaloids from RC were compared by feeding the mice for 8 weeks with a dosage of 105 mg/kg while the dose-dependent study (35 mg/kg and 105 mg/kg) of JAT on obese mice was conducted in another 8-week-long animal experiment. Meanwhile, RNA-seq analysis, in vitro experiments, and western blotting were utilized to predict and confirm the potential pathway that JAT participated in improving obesity. Results: The experimental results demonstrated that five RC alkaloids caused different degrees of weight loss in db/db obese mice. Among them, JAT showed the best effect. It could significantly reduce the body weight, blood lipid levels, and epididymal fat weight of db/db mice. H&E and Oil red O staining results showed that it could also dramatically improve liver lipid metabolism. The results from RNA-seq suggested that JAT had significantly altered 207 DEGs for the treatment of obesity, among which IRS1 changed the most. Next, GO and KEGG analysis enriched four major lipid metabolism-related pathways: biosynthesis of unsaturated fatty acids, PI3K-AKT signaling pathway, metabolic pathways, and fatty acid elongation. Finally, in vitro experiments and western blotting proved that JAT regulated the expression of IRS1/PI3K/AKT pathway-related proteins in a dose-dependent manner to address obesity. Conclusions: In conclusion, JAT from RC has an effect on treating obesity, and its anti-obesity effect may be exerted via the IRS1/PI3K/AKT signaling pathway. Graphical abstract: Image 1 Highlights: Jatrorrhizine (35 mg/kg and 105 mg/kg) showed the best amelioration of obesity and hepatic steatosis in high-fat diet-induced db/db mice among five alkaloids of Rhizoma Coptidis (berberine, epiberberine, palmatine, coptisine and jatrorrhizine). Transcriptomic analysis revealed a cluster of 207 genes that were robustly regulated by JAT treatment in the liver of db/db mice, these genes mainly enriched in lipid metabolism-related signaling pathways. Jatrorrhizine exerted anti-obesity effect through IRS1/PI3K/AKT signaling pathway (up-regulates IRS1, PI3K, p-AKT/AKT expression; down-regulates SREBP-1c expression).